2020
DOI: 10.1029/2020gc009359
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Magmatic Heating of the Lithosphere Beneath the Hawaiian Islands Inferred From Salt Lake Crater Mantle Xenoliths

Abstract: Volcanic activity along the Hawaiian-Emperor chain has persisted for at least 82 Myrs and is considered to be one of the most prominent surface expressions of a hot spot caused by a mantle plume (Wolfe et al., 2009). Hawaiian volcanism is subdivided into four sequential stages: preshield, shield, postshield, and rejuvenation (Clague & Dalrymple, 1987). Rejuvenated volcanism is a perplexing phenomenon during which magmatism occurs after a 0.5-2 Myr hiatus in volcanism at a substantial distance (>100 km) away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…1C]. This thinner lithosphere is consistent with flexural and gravimetric observations, as well as with xenolith-based thermobarometric results, which indicate that temperatures of 1000° to 1100°C occur at depths of 45 to 55 km beneath Hawaii ( 33 , 34 ). In contrast to the Icelandic example, this discrepancy suggests that, locally, zLAB1 is notably shallower than expected beneath Hawaii.…”
Section: Resultssupporting
confidence: 87%
“…1C]. This thinner lithosphere is consistent with flexural and gravimetric observations, as well as with xenolith-based thermobarometric results, which indicate that temperatures of 1000° to 1100°C occur at depths of 45 to 55 km beneath Hawaii ( 33 , 34 ). In contrast to the Icelandic example, this discrepancy suggests that, locally, zLAB1 is notably shallower than expected beneath Hawaii.…”
Section: Resultssupporting
confidence: 87%
“…The lack of features beneath the swell in this depth range shows that the excess elevation is not created by reheating or replacement of the upper lithosphere. Note that we have no doubt about local reheating around deep magma chambers, as observed by mantle xenoliths from the island of Oahu (Guest et al., 2020); however, these results are not applicable to the main, broad swell. Dehydration of the newly formed lithosphere during seafloor spreading is expected at depths shallower than about 70 km (Hirschmann, 2010; Katz et al., 2003) by migration of the pressure‐release melt to the surface to form the crust.…”
Section: Resultsmentioning
confidence: 60%
“…We must also address that other studies have suggested lab-derived low-temperature plasticity is perfectly consistent with Earth's lithosphere, and rather does not reproduce observations of flexure at Hawaii because thermal erosion by the Hawaiian plume significantly weakens the Hawaiian lithosphere by modifying the ∼90 Myr thermal structure (Guest et al, 2020;Hunter & Watts, 2016;Pleus et al, 2020). This would cause viscoelastic loading models to overestimate lithospheric strength and underestimate flexure if they do not account for the anomalous thermal structure.…”
Section: Rheological Equationsmentioning
confidence: 91%